Separation and pre-concentration of Sunset Yellow in beverages and effervescent vitamin C tablets by a new flotation technique prior to spectrophotometric determination. Issue 11 (2nd November 2019) - Soleymani, Bahram; Zargar, Behrooz; Rastegarzadeh, Saadat
ABSTRACT: A new, simple, low cost, high efficiency, and rapid floating technique was developed for the determination of Sunset Yellow in beverage and effervescent vitamin C. The method is based on two main steps: 1)- formation of dye-surfactant complex by the addition of a cationic surfactant, cetyltrimethylammonium bromide, to the solution containing an anionic dye (Sunset Yellow) and 2)- flocculation of the dye-surfactant complex with the participation of sodium perchlorate as a coagulant followed by aggregation and enlargement of the flocs while floating at the top of the solution. After the extraction, separated and preconcentrated Sunset Yellow was investigated by spectrophotometric determination. IR spectrum, scanning electron microscopy (SEM), and light microscopy were used to characterise the flocs. The effects of different parameters such as pH, concentration of surfactant, concentration of sodium perchlorate, and temperature on the extraction of dye were investigated and optimized. Under optimum conditions, a linear calibration curve was obtained in the range of 0.05–5 mg L −1 . The detection limit (3Sb/m ) was 0.02 mg L −1 with a preconcentration factor of 25. The relative standard deviation (RSD) for 0.1 mg L −1 of Sunset Yellow was 2.6% (n = 10). The applicability of the method was evaluated by measuring the amount of dye in beverage and effervescent vitamin C. Interferences of typical cations and anions which may participate in the matrices were also checked. The amount of Sunset Yellow found in real samples was 1.32–3.89 mgL −1 . Graphical Abstract: